Efficacy, safety and tolerability of rivaroxaban for the secondary prevention of stroke in patients with atrial fibrillation in clinical practice. (December 2015) - Monteagudo, María; Fernández-Díaz, Eva; García-García, Jorge; Ayo-Martín, Óscar; Hernández-Fernández, Francisco; Segura, Tomás
Aim: To evaluate the efficacy, safety and tolerability of rivaroxaban for the secondary prevention of stroke in patients with atrial fibrillation in clinical practice.Methods: Patients treated with rivaroxaban for secondary prevention of stroke/transient ischemic attack attended at a cerebrovascular disease unit were consecutively included in a noninterventional and prospective study.Results: 89 patients (median age 77 years, CHADS2 = 4, HAS-BLED = 3, follow-up = 15 months) were included. Rivaroxaban was started early after the cerebrovascular event (median 5 days for stroke and 3 days for transient ischemic attack). Stroke recurrence occurred in only one patient (annual rate, 0.82%). Eight cases of clinically significant bleeding were recorded (annual rate, 6.58%), of which two were major (annual rate, 1.64%) and one intracranial (annual rate, 0.82%). Medication persistence was very good.Conclusion: Our data show that the early treatment with rivaroxaban is well tolerated, efficacious and safe for secondary prevention of real-life atrial fibrillation patients.